Students™ creativity dimension in chemistry e-module based on augmented reality with project based learning approach - Harefa, Nelius; Sumiyati, Sumiyati; Tamba, Riris Marito (Pascasarjana Universitas Negeri Medan, 2024)
The dimension of creativity is an important aspect that must be developed in the learning process. A good dimension of creativity will stimulate students to produce creative, innovative and applicable products. In this study, analysis and interpretation of the dimensions of creativity were carried out which consisted of disciplined, imaginative, inquisitive, persistent, and collaborative. The analysis and interpretation is carried out through a project-based learning approach integrated with augmented reality. The research was conducted at SMA Negeri 2 Jonggol, West Java, in class XI SMA with a total sample of 148 people. The results of interpretation and analysis of research data show that the average score of the dimensions of creativity is 78.6 in the high category, where the highest average score is in the persistent element of 80.04 in the very high category and the lowest average score is in the inquisitive element of 76.68 in the high category. In general, the implementation of a project-based learning approach integrated with augmented reality is able to stimulate an increase in the dimensions of student creativity.